Occupational safety and health management systems as a component of labor productivity (2022)
The Occupational Health and Safety Management System (SG-SST) encompasses a discipline that aims to improve working conditions and the work environment, which leads to the inclusion of policy, planning, evaluation, improvement actions continuous and promotion of the maintenance of the physical, mental, and social well-being of the employees in the workspaces. Therefore, the objective of the article is to analyze the occupational safety and health management system (SGSST) as a component of labor productivity of small and medium-sized enterprises (SMEs), exporters of the metal-mechanic sector of Barranquilla-Colombia. Methodologically, it is developed under the quantitative paradigm, non-experimental design, cross-sectional and descriptive scope. The results determine that in this type of companies the SGSST are developed from the conception of security programs. The degree of commitment of the strategic direction in promoting the effectiveness of the programs is evident, but it is necessary to consolidate processes for the adoption and awareness of these, by the employees promoting labor productivity. It is recommended the implementation of strategies that guarantee compliance with the SGSST, generating a high impact on productivity processes.